Hydrogenation of Biomass-derived 5-hydroxymethylfurfural (HMF) over Pd Catalysts in Aqueous Medium - da Silva, Wesley Romário; Rosolen, José Maurício; Donate, Paulo Marcos (Orbital: The Electronic Journal of Chemistry, 2022)
We hydrogenated biomass-derived 5-hydroxymethylfurfural (HMF) in aqueous medium in a reaction catalyzed by palladium nanoparticles (Pd) on carbonaceous materials with different morphology and hydrophobic degree. The Pd catalysts were prepared by dipping the carbonaceous material into a Pd0 micro-emulsion. The catalyst support affected catalytic HMF hydrogenation. By using micrometric active carbon (AC) combined with cup-stacked carbon nanotubes (CSCNTs) and Pd, we obtained a micro/nanostructured material designated Pd/CSCNT-AC, which performed better than the other carbonaceous materials containing similar Pd loading. Pd/CSCNT-AC catalyzed HMF hydrogenation at the C=O double bond more selectively, giving between 85% and 99% selectivity toward 2,5-bis(hydroxymethyl)furan (BHMF). We also investigated how temperature, hydrogen pressure, and reaction time affected HMF hydrogenation.